GEOPOLITICS OF COVID-19 VACCINES - A NEW COLD WAR OF THE ‘VACCINE SUPERPOWERS’? - Dokmanović, Mirjana; Cvetićanin, Neven (Journal of Regional Security, 2022)
The COVID-19 pandemic has proved the claim of Alan Ingram (2005) that a disease is a geopolitical issue. Many authors have recognized that states, particularly the most powerful ones (the US, China, Russia), use the current global crisis to strengthen their influence worldwide in line with their geopolitical, economic, and military aspirations. This paper is aimed to inquiry do they use the COVID-19 vaccines for the same purpose. The implemented methods include a geopolitical approach, a comparative method, and a qualitative content analysis of collected statements of statemen and media narratives published from 13 December 2020 to 13 February 2021. The findings indicate that the vaccines have become a geopolitical tool. Due to a new Cold War of the ‘vaccine superpowers’, the world became divided in Western and Eastern ‘vaccine-blocks’. However, in the background of this ‘battle over vaccines’, a possible future cooperation of the West and the East may emerge.